Electrochemical reduction of CO 2 over Sn-Nafion ® coated electrode for a fuel-cell-like device - Prakash, G.K. Surya (2013)
Commercially available Sn particles mixed with Nafion ® ionomer are used to prepare an electrode with a gas diffusion layer support in a manner similar to that in which fuel cell electrodes are prepared. Cyclic voltammetry is performed in aqueous NaHCO 3 (basic medium) on the electrode and the Tafel parameters are obtained and compared with a Sn metal disc and with a graphite disc coated with Sn powder. In addition, electrolysis is carried out potentiostatically, also in NaHCO 3 solution, at various potentials. The exchange current density on the Sn/gas diffusion layer electrode shows to be two orders of magnitude higher that on the metallic Sn disc. The maximum current density obtained during electrolysis is 27 mA cm -2 at -1.6 V vs. NHE, with 70% faradaic efficiency towards the formation of formate, which is one of the highest values found in the literature on Sn electrode at ambient pressure. © 2012 Elsevier B.V. All rights reserved.